Incidence and Audit of Treatment on Third and Fourth Grade Perineal Tear - Santoso,, Budi I; Pamungkas, Satriyo (Indonesian Journal of Obstetrics and Gynecology, 2017)
Objective: To describe the incidence of 3rd and 4th grade perineal tear in Dr. Cipto Mangunkusumo hospital on the period of 2011 - 2014 and its compatibility of treatment based on RCOG guidelines. Methods: Data were collected through medical records on women who had vaginal delivery in Dr. Cipto Mangunkusumo hospital from January 2011 to December 2014. This was a descriptive study with cross sectional design. Results: The incidence of 3rd and 4th grade perineal tear each year were 3.55%, 4.35%, 3.95%, and 1.77% consecutively. About 100% treatment were accompanied by consultant; 3.5% performed in operating theatre; 90.7% were given postoperative antibiotic; 42.2% were given urinal catheter in 1x24 hour postoperative; 100% were given analgesic. About 61.4% of procedures were not compatible with RCOG guidelines. Conclusion: The study showed that the incidence of 3rd and 4th grade of perineal tear was 3.66% for 4 years and the compliance to RCOG standard was 38.6%. [Indones J Obstet Gynecol 2017; 5-1: 35-41] Keywords: incidence, RCOG, third and fourth grade of perineal tear, treatment